Track analysis of the funnel-web spiders (Araneae: Agelenidae) of Mexico - Julieta Maya-Morales; María Luisa Jiménez; Juan J. Morrone (Revista Mexicana de Biodiversidad)
We analyzed distributional data of 59 species of funnel-web spiders (Araneae: Agelenidae) of Mexico. We constructed individual tracks for the species analyzed, based on published and unpublished records, and based on their overlap we obtained 9 generalized tracks. Three generalized tracks belong to the Californian Nearctic dominion (Nearctic region) and 6 generalized tracks extend along the Mexican transition zone. Seven generalized tracks are defined by species of the same genus or closely related genera and 2 generalized tracks are supported by species of distantly related genera, which shows that both spatial relationships and phylogenetic evidence support the existence of ancestral biotas including unrelated taxa.